Effects of Meditation on Symptoms of Knee Osteoarthritis - Selfe, Terry Kit (Altern Complement Ther, 2013)
OBJECTIVE: The aim of this study was to investigate changes in knee pain, function, and related indices in older adults with osteoarthritis (OA) of the knee, following an 8-week meditation program. METHODS: Eleven community-dwelling adults with physician- confirmed knee OA were enrolled in the study. Core outcomes included recommended measures of knee pain (Western Ontario and McMaster Universities Osteoarthritis Index [WOMAC] and 11-point numeric rating scale [NRS]), function (WOMAC), and perceived global status (patient global assessment). Additional outcomes included: perceived stress; stress hardiness; mood; sleep; and sympathetic activation. Following baseline assessment, participants were trained briefly in mantra meditation and instructed to meditate for 15–20 minutes twice daily for 8 weeks, and to record each practice session on a daily log. Changes over time were analyzed using paired t-tests. RESULTS: Nine participants (82%) completed the study. Participants had statistically significant improvements in all core outcomes: knee pain (WOMAC: 47.7% ± 25.1% reduction, P = 0.001; NRS: 42.6% ± 34.6% reduction, P < 0.01); function (44.8% ± 29.9, P = 0.001); and global status (45.7% ± 36.5, P = 0.01); as well as knee stiffness (P = 0.005), mood (P = 0.05), and a WOMAC proxy for sleep disturbance (P = 0.005). CONCLUSIONS: Findings from this pilot study suggest that a mantra meditation program may help reduce knee pain and dysfunction, as well as improving mood and related outcomes in adults with knee OA.